COVID‐19 and impacts on global food systems and household welfare: Introduction to a special issue. (4th May 2021) - Swinnen, Johan; Vos, Rob
Abstract: The food system, and those who depend on it, have been strongly but unevenly affected by COVID‐19. Overall, the impacts on food systems, poverty, and nutrition have been caused by a combination of a generalized economic recession and disruptions in agri‐food supply chains. This paper provides an overview of the contributions to this Special Issue of Agricultural Economics . The papers in this volume confirm that both income shocks and supply disruptions have affected food security and livelihoods the most where supply chains were more poorly integrated, and poverty and market informality had greater presence before COVID‐19. Yet, as the pandemic still has societies worldwide in a stranglehold, outcomes remain uncertain and reliable data are still sparsely available. This Special Issue of Agricultural Economics provides new insights of the pandemics impact on food systems, household welfare, and food security, building on both model‐based scenario analysis and new survey data. These methods have proven helpful in providing these insights amidst the unprecedented shock that the pandemic has caused to production systems and livelihoods worldwide. However, they also suffer from obvious limitations identified in this editorial overview paper and require substantial improvement in order to understand the changes in economic behavior and functioning of food supply chains induced by the pandemic.